Online Decision Making in Crowdsourcing Markets: Theoretical Challenges - Slivkins, Aleksandrs; Vaughan, Jennifer Wortman (ACM SIGecom Exchanges, 2013)
Over the past decade, crowdsourcing has emerged as a cheap and efficient method of obtaining solutions to simple tasks that are difficult for computers to solve but possible for humans.
Position paper and survey.